The influence of dynamic loading and thermal conditions on tram track slab damage resulting from subgrade differential settlement. (October 2021) - Shan, Yao; Wang, Binglong; Zhang, Jiawei; Zhou, Shunhua
Highlights: A novel constraint application method is presented for track irregularity evaluation. A staggered iterative algorithm is improved for settlement induced pad forces. A sequentially coupled thermal-stress analysis procedure is proposed. The damage characteristics of the slab due to multiple issues are investigated. The criterion of subgrade differential settlement of the tram track is proposed. Abstract: To guarantee the operation safety of the tram in typical soft soil area, the damage characteristics of tram track slabs due to subgrade differential settlement, dynamic train loads and environmental issues are investigated in this work. A three-dimensional (3D) finite element analysis (FEA) model is utilized to calculate the additional track vertical profile irregularity due to the subgrade differential settlement. The overall rail vertical profile irregularities are employed as excitations of a tram vehicle-track-subgrade coupling model to calculate the dynamic pad forces. After that, a sequentially coupled thermal-stress analysis procedure is proposed to evaluate the initial stress-damage field of the slabs resulting from environmental temperature variation. The plastic damage theory is adopted to investigate the damage characteristics of tram track slabs due to multiple issues. According to the damage factors calculated from this model, the criterion of subgrade differential settlement of the tram track is proposed. The damage state of the tram track is suggested to be a key factor of the subgrade differential settlement control system.